PERILAKU MINUM TEH DAN KADAR HEMOGLOBIN (Hb) PADA SISWA-SISWI SEKOLAH MENENGAH KEJURUAN NEGERI 1 JORLANG HATARAN DESA DOLOK MARLAWAN KECAMATAN JORLANG KABUPATEN SIMALUNGUN TAHUN 2012 - Emma Bermila Bangun; Zulhaida Lubis; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Tea has a lot of the nutrients for body such as polyphenols, tannins, vitamins and minerals, but the function of tannins in tea can be a barrier to the absorption of iron when tea is consumed at meals. If the absorbtion of iron is impared and a little iron consumption, the body will have iron deficiency can lead to low hemoglobin levels or anemia. The purpose of this study is to determine the behavior of drinking tea and hemoglobin (Hb) levels of students in Vocational High School 1 Jorlang Hataran Marlawan Dolok village. This research is descriptive study. The population of this study were the students of class X, XI and XII The Vocational High School 1 Jorlang Hataran Marlawan Dolok village. Samples were taken 80 people with simple random technique. The data was collected using questionnaires with the form of 24-hour food recall. Results showed that behavior about tea and hemoglobin levels of students in The Vocational High School 1 Jorlang Hataran Marlawan Dolok village almost entirely at the level of moderate tea consumption was 73.80% and the rate of 23.70% by weight of tea consumption, with hemoglobin levels also largely normal and anemic as much as 83.05% in moderate tea consumption and 63.16% by weight of tea consumption. Based on the results of this study suggested to the students in The Vocational High School 1 Jorlang Hataran Marlawan Dolok village to reduce the consumption of tea, especially when in conjunction with eating and increased nutrient intake by choosing foods that are more diverse. keywords: tea consumptions, hemoglobin levels, vocational students